Length-Weight Relationship, Condition Factor and Otolith Morphometric of Serranus cabrilla from the East Libya Mediterranean Sea Coast - Alfergani, Eman Salem; El-Mabrok, Mohammad; Mostafa , Sokaina Muloud; Ahmed, Rasha Momen (Journal of Fisheries and Environment, 2024)
This study investigated the length-weight relationship, condition factor, and otolith morphometrics of Serranus cabrilla specimens captured near the Benghazi coast, Libya, during spring 2021. Total body length (TL), total weight (TW), and otolith dimensions were measured. The mean TL and TW were 15.06±0.12 cm and 41.87±1.13 g, respectively. The regression coefficient (2.72) for the length-weight relationship was not significantly different from 3 according to the t-test (b = 3, p≥0.05), indicating that growth is isometric. Fulton's condition factor (Kf) ranged from 0.77 to 1.81 (mean = 1.20±0.01), and the relative condition factor (Kn) ranged from 0.65 to 1.48 (mean = 1.02±0.01). S. cabrilla otoliths exhibited a fusiform shape with a heterosulcoid sulcus, characterized by a funnel-shaped ostium and a tubular cauda. No significant differences (p≥0.05) were observed between left and right otoliths, so the left otolith was used for subsequent analyses. The otolith length constituted 3.51% of TL, and the height-to-length ratio averaged 42.71±0.39%. Based on relative size (0.36±0.00), the otoliths were classified as medium-sized. Ellipticity, rectangularity, and roundness values were 0.40±0.03, 0.67±0.00, and 0.37±0.00, respectively. The strongest correlation was observed between body length and otolith length.